2020
DOI: 10.1364/oe.386356
|View full text |Cite
|
Sign up to set email alerts
|

Ring resonator enhanced mode-hop-free wavelength tuning of an integrated extended-cavity laser

Abstract: Extending the cavity length of diode lasers with feedback from Bragg structures and ring resonators is highly effective for obtaining ultra-narrow laser linewidths. However, cavity length extension also decreases the free-spectral range of the cavity. This reduces the wavelength range of continuous laser tuning that can be achieved with a given phase shift of an intracavity phase tuning element. We present a method that increases the range of continuous tuning to that of a short equivalent laser cavity, while … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 46 publications
(67 reference statements)
2
50
0
Order By: Relevance
“…It should be noted that the sweeping range (or modulation speed) should be evaluated in combination with the laser longitudinal mode spacing. As for a fixed phase shift (or driving signal amplitude), the laser frequency shift is proportional to the longitudinal mode spacing [31]. In this study, the measured longitudinal mode spacing is 4.5 GHz, slightly smaller than the simulation.…”
Section: Thermal Tuning Performancementioning
confidence: 56%
See 3 more Smart Citations
“…It should be noted that the sweeping range (or modulation speed) should be evaluated in combination with the laser longitudinal mode spacing. As for a fixed phase shift (or driving signal amplitude), the laser frequency shift is proportional to the longitudinal mode spacing [31]. In this study, the measured longitudinal mode spacing is 4.5 GHz, slightly smaller than the simulation.…”
Section: Thermal Tuning Performancementioning
confidence: 56%
“…It should be noted that since the longitudinal mode shifts within the passband of the Vernier filter, there is slight power variation during the sweep. If the electrical signals are applied to both the MRRs and the phase shifter, a wider frequency tuning range without power variation can be obtained [31]. Table 1 compares the performance of this work with other Si3N4 and silicon ECLs with a similar configuration reported in the literature.…”
Section: Thermal Tuning Performancementioning
confidence: 93%
See 2 more Smart Citations
“…Note, that this wavelength tuning is discrete and that the mode-hop-free tuning range is far smaller. Typically our hybrid integrated laser can be tuned a few 10s of picometers before a mode-hop occurs, however, it has recently been shown that the mode-hop-free tuning range can be increased by simultaneously tuning the phase section (see Figure 3) of the laser and a mode-hop-tuning range of 0.22 nm has been reported [18]. For many application the noise characteristics of the laser modules are critical.…”
Section: Laser Characteristicsmentioning
confidence: 99%